Record of Banded Leopard Blowfish Arothron leopardus (Day, 1878) (Tetraodontiformes: Tetraodontidae) from Muvattupuzha River, Kerala, India - Zeena, K. V.; Jameela Beevi, K. S. (Journal of the Bombay Natural History Society (JBNHS), 2012)
No Abstract.